2019
DOI: 10.3389/fgene.2019.00851
|View full text |Cite
|
Sign up to set email alerts
|

Consensus-Expressed CXCL8 and MMP9 Identified by Meta-Analyzed Perineural Invasion Gene Signature in Gastric Cancer Microarray Data

Abstract: As an underrecognized route of cancer metastasis, perineural invasion (PNI) is defined as the neoplastic invasion of nerves, which can be targeted to inhibit the metastasis of malignant cancer. However, the mechanism underlying PNI in cancer is largely unknown. We constructed a PNI gene signature based on a Pathway Studio-mediated literature screen and investigated the relevant genes in a gastric cancer model. Thus, a total of 467 studies/datasets were retrieved from the Gene Expression Omnibus database using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Studies have found that CXCL8 is predominantly secreted by macrophages and contributes to the immunosuppressive microenvironment by inducing PD-L1+ macrophages in GC [ 60 ]. CXCL8 could be an early detection marker for perineural invasion-related GC, with a potential to be utilized as individual therapy targets [ 61 ]. CXCL8 inhibitors may drive antitumor response, providing potential therapeutic effects for patients with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that CXCL8 is predominantly secreted by macrophages and contributes to the immunosuppressive microenvironment by inducing PD-L1+ macrophages in GC [ 60 ]. CXCL8 could be an early detection marker for perineural invasion-related GC, with a potential to be utilized as individual therapy targets [ 61 ]. CXCL8 inhibitors may drive antitumor response, providing potential therapeutic effects for patients with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The same results were also confirmed in prostate cancer 9 , knockout of CXCL8 in PC-3M-LN4 cells decreased the expression of MMP9, while up-regulation of CXCL8 increased the expression of MMP9. A study on the analysis of gastric cancer microarray data showed that the co-expression of CXCL8 and MMP9 could be an early detection marker of perineural invasion(PNI) 27 . To sum up, these three hub genes are of great value and significance as tumor markers and prognostic indicators of ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…However, gastric mucosal cell malignancy results in CLDN18.2 epitope exposure and enables it to become a target unique to cancer cells [13]. Zolbetuximab is a chimeric monoclonal antibody that targets CLDN18.2 epitopes and initiates cell death by antibody-dependent cellular cytotoxicity and complement-dependent cytotoxicity [17]. In a phase I trial, Zolbetuximab showed single-agent efficacy and manageable toxicity in patients with heavily pretreated advanced CLDN18.2-positive gastric/gastroesophageal junction (G/GEJ) cancer [17].…”
Section: Targeting Claudin 182 With Zolbetuximab (Imab362)mentioning
confidence: 99%
“…Zolbetuximab is a chimeric monoclonal antibody that targets CLDN18.2 epitopes and initiates cell death by antibody-dependent cellular cytotoxicity and complement-dependent cytotoxicity [17]. In a phase I trial, Zolbetuximab showed single-agent efficacy and manageable toxicity in patients with heavily pretreated advanced CLDN18.2-positive gastric/gastroesophageal junction (G/GEJ) cancer [17]. Furthermore, in a phase II trial, Zolbetuximab monotherapy exhibited antitumor activity in patients sharing the same cancer parameters [18].…”
Section: Targeting Claudin 182 With Zolbetuximab (Imab362)mentioning
confidence: 99%